Channel Assignment Algorithms and Strategies for Wireless Mesh Networks - Maliha Amir Ali Charania; Husnain Mansoor Ali (JISR on Computing, 2013)
This research report is about providing a solution to the problem of channel assignment in the multi radio wireless mesh networks that have an ad hoc based infrastructure. The aim was to minimize the fractional interference so that throughput can be maximized. The algorithms to solve this problem were classified and explained how they work. A description of channel assignment techniques is given along with a brief comparison in the literature. Main focus was towards the use on genetic algorithm. It also gives a detailed explanation of how genetic algorithm could be implemented in order to solve this problem along with conflict graphs being made by running functions in MATLAB.